The clinical method in general surgery - Antonio Ríos Rodríguez; Reinaldo Jiménez Prendes (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
The final aim of medicine is the treatment of diseases, but this beautiful effort can not be exercised without the prior establishment of a diagnosis, so we think that our main task is to establish the nature of the condition we are going to be dealing with in each case. The retaking of the clinical method in general surgery in order to provide a quality health service is the major objective of this paper.